How temperature and aridity drive lignin decomposition along a latitudinal transect in western Siberia ... - Dao, Thao Thi; Mikutta, Robert; Wild, Birgit; Sauheitl, Leopold; Gentsch, Norman; Shibistova, Olga; Schnecker, Jörg; Lashchinskiy, Nikolay; Richter, Andreas; Guggenberger, Georg (Oxford [u.a.] : Wiley-Blackwell, 2023)
Climate change drives a northward shift of biomes in high-latitude regions. This might have consequences on the decomposition of plant litter entering the soil, including its lignin component, which is one of the most abundant components of vascular plants. In order to elucidate the combined effect of climate and soil characteristics on the decomposition pattern of lignin, we investigated lignin contents and its degree of oxidative decomposition within soil profiles along a climosequence in western Siberia. Soil samples were collected from organic topsoil to mineral subsoil at six sites along a 1500-km latitudinal transect, stretching from tundra, through taiga and forest steppe to typical steppe. The stage of lignin degradation, as mirrored by decreasing organic carbon-normalized lignin contents and increasing oxidative alteration of the remnant lignin (acid-to-aldehyde ratios of vanillyl- and syringyl-units [(Ac/Al)V and (Ac/Al)S]) within soil horizons, increased from tundra to forest steppe and then ...